Physical Quality Observation of Edible Coating Made from Aloe Vera on Cantaloupe (Cucumismelo L.) Minimally Processed - Yulianingsih, R.; Maharani, D.M.; Hawa, L.C.; Sholikhah, L. (Pakistan Journal of Nutrition, 2013)
Minimally processed fruits, which provide fresh and edible product, are facing some difficulties on damages such as progressive deterioration due to desiccation, microbial growth and bio chemical processes. To overcome these problems the application of edible coating from aloe vera suggests a proper assistance. An edible coating from aloe vera was developed and tested on minimally processed cantaloupe fruit for the extension of shelf-life. A coating from aloe vera with 0.02% ascorbic acid, 1% Glycerol and 1.5% CMC (Carboxymethyl Cellulose) was applied on minimally processed cantaloupe. Cantaloupes coated with the aloe vera were stored at 5, 10, 15, 20 and 27°C for 24, 48, 76 and 96 hours. Weight loss, hardness and color of cantaloupes were measured to determine the ability of aloe vera in protecting the cantaloupes from deterioration after storing at the various conditions. The applications of coating from aloe vera on cantaloupe were shown reducing weight loss and color changes and effective in retaining the firmness of the minimally processed cantaloupe.